Knowledge Actors and Transnational Governance - Stone, D. author. aut Link
XVI, 222 p.
Keywords: Diane Stone addresses the network alliances or partnerships of international organisations with knowledge organisations and networks. Moving beyond more common studies of industrial public-private partnerships, she addresses how, and why, international organisations and global policy actors need to incorporate ideas, expertise and scientific opinion into their 'global programmes'. Rather than assuming that the encouragement for 'evidence-informed policy' in global and regional institutions of governance is an indisputable public good, she queries the influence of expert actors in the growing number of part-private or semi-public policy networks.